2018
DOI: 10.1016/j.ajme.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and associated factors among patients with diabetes mellitus in Botswana

Abstract: Background: Health-related quality of life (HRQOL) is an important aspect of diabetes mellitus care. The objective of the study was to determine the HRQOL of diabetes mellitus (DM) patients in Botswana as little known in Africa. Materials and methods: A cross-sectional study of 380 randomly selected DM patients in a tertiary clinic in Gaborone, Botswana was conducted to obtain Data on HRQOL and structured questionnaire was used to collect information on sociodemographic and clinical characteristics. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
64
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 65 publications
12
64
4
2
Order By: Relevance
“…While some studies have shown that long duration of diabetes is associated with decreased quality of life, which is consistent with the present study findings, other studies showed no association between the two variables …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…While some studies have shown that long duration of diabetes is associated with decreased quality of life, which is consistent with the present study findings, other studies showed no association between the two variables …”
Section: Discussionsupporting
confidence: 92%
“…Some studies reported that patients who had poor glycemic control had a diminished HRQoL . Other studies did not report a significant association between glycemic control and HRQoL, which is consistent with the current study findings. A possible explanation for the lack of association between glycemic control and the EQ‐5D scores is that there is a time delay between elevated HbA1c and the development of debilitating complications.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The demographic characteristics of the participants, including nonelderly age, female, low education level, and inactive work life, were similar to the findings of Rwegerara et al, showing that the majority of DM patients were women (69.5%), had a first-degree education (47.6%), were <54 years of age (41.8%), and had a disease duration of <5 years (49.2%). Vidal-Peracho et al also observed that the majority of patients with T2DM were female (74%) and inactive (89.6%) [18][19].…”
Section: Discussionmentioning
confidence: 87%